Detrimental impact of sulfide on the seagrass Zostera marina in dark hypoxia. - Harald Hasler-Sheetal (PLoS ONE, 2023)
Sulfide poisoning, hypoxia events, and reduced light availability pose threats to marine ecosystems such as seagrass meadows. These threats are projected to intensify globally, largely due to accelerating eutrophication of estuaries and coastal environments. Despite the urgency, our current comprehension of the metabolic pathways that underlie the deleterious effects of sulfide toxicity and hypoxia on seagrasses remains inadequate. To address this knowledge gap, I conducted metabolomic analyses to investigate the impact of sulfide poisoning under dark-hypoxia in vitro conditions on Zostera marina, a vital habitat-forming marine plant. During the initial 45 minutes of dark-hypoxia exposure, I detected an acclimation phase characterized by the activation of anaerobic metabolic pathways and specific biochemical routes that mitigated hypoxia and sulfide toxicity. These pathways served to offset energy imbalances, cytosolic acidosis, and sulfide toxicity. Notably, one such route facilitated the transformation of toxic sulfide into non-toxic organic sulfur compounds, including cysteine and glutathione. However, this sulfide tolerance mechanism exhibited exhaustion post the initial 45-minute acclimation phase. Consequently, after 60 minutes of continuous sulfide exposure, the sulfide toxicity began to inhibit the hypoxia-mitigating pathways, culminating in leaf senescence and tissue degradation. Utilizing metabolomic approaches, I elucidated the intricate metabolic responses of seagrasses to sulfide toxicity under in vitro dark-hypoxic conditions. My findings suggest that future increases in coastal eutrophication will compromise the resilience of seagrass ecosystems to hypoxia, primarily due to the exacerbating influence of sulfide.